The effect of deep inhalation on mannitol responsiveness. Issue 3 (14th December 2019) - Blais, Christianne M.; Davis, Beth E.; Cockcroft, Donald W.
Abstract: Background: Mannitol inhalation testing is specific for asthmatics with eosinophilic airway inflammation, a factor that has been negatively correlated with the development of deep inhalation bronchoprotection. Objective: To evaluate the effect of deep inhalations on responsiveness to inhaled mannitol in correlation with the degree of airway inflammation. Methods: Twenty participants with stable asthma completed this randomized, crossover study. A screening visit assessed responsiveness to methacholine and airway inflammation through fractional exhaled nitric oxide (FeNO) measures and sputum induction. Participants next completed two mannitol challenges, one with deep inhalations (standard method) and one with inhalations to half of total lung capacity, and two methacholine challenges, one with tidal breathing (standard method) and one with deep inhalations. Only the inhalation technique for dose administration differed between repeat mannitol or methacholine challenges. Results: Deep inhalations did not significantly influence the provocative dose of mannitol causing a 15% fall in forced expiratory volume in 1 second (( P = .73; n = 7) or the mannitol dose‐response slope ( P = .26; n = 20). Deep inhalations produced significant bronchoprotection against methacholine ( P = .03; n = 20). FeNO levels were significantly correlated to sputum eosinophilia ( P = .02; n = 15), responsiveness to deep inhalation methacholine ( P = .005; n = 20), the dose‐response slopes from deep inhalation mannitol ( P = .01; n = 20), and the dose‐response slope from non–deep inhalation mannitol ( P = .005; n = 20). Conclusions and Clinical Relevance: Deep inhalations did not produce significant bronchoprotection against inhaled mannitol. This result is in agreement with past findings linking airway inflammation with loss of deep inhalation bronchoprotection. Clinical Trial Registration: This study was prospectively registered on clinicaltrials.gov (NCT 03505489).